2017
DOI: 10.1177/2398212817694888
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy, organisation and development of contralateral callosal projections of the mouse somatosensory cortex

Abstract: Background: Alterations in the development of neuronal connectivity can result in dramatic outcomes for brain function. In the cerebral cortex, most sensorimotor and higher-order functions require coordination between precise regions of both hemispheres through the axons that form the corpus callosum. However, little is known about how callosal axons locate and innervate their contralateral targets. Methods: Here, we use a combination of in utero electroporation, retrograde tracing, sensory deprivation and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…3) and is the peak of upper layer (L2/3) neurogenesis (30). All animals for this and subsequent in vivo manipulations were collected at stage 28 (P10 mouse, P50 dunnart), an age at which long-range projection patterns are well established in the brain of both species (30,32). We confirmed that overexpression of either construct resulted in an increase of CTIP2 immunofluorescence in electroporated cells, as compared with control electroporated cells ( Fig.…”
Section: The Ectopic Overexpression Of Either Mouse-or Dunnart-specifsupporting
confidence: 62%
“…3) and is the peak of upper layer (L2/3) neurogenesis (30). All animals for this and subsequent in vivo manipulations were collected at stage 28 (P10 mouse, P50 dunnart), an age at which long-range projection patterns are well established in the brain of both species (30,32). We confirmed that overexpression of either construct resulted in an increase of CTIP2 immunofluorescence in electroporated cells, as compared with control electroporated cells ( Fig.…”
Section: The Ectopic Overexpression Of Either Mouse-or Dunnart-specifsupporting
confidence: 62%
“…7E). Importantly, such an arrangement of intermingled commissural neurons with homotopic and heterotopic targets, with only few cells that demonstrate long-range contralateral branches, has also been reported in callosal neurons of rodents and primates (32)(33)(34). These findings, together with anterograde evidence of contralateral axons terminating in both homotopic and heterotopic targets in both marsupials and eutherians, suggest that the mechanisms of contralateral axon targeting include both positional and nonpositional cues (35).…”
Section: Resultsmentioning
confidence: 53%
“…In all eutherians studied to date, including rodents, carnivores, monkeys, and humans, the axons that form the corpus callosum are spatially segregated within the tract into rostrocaudal and dorsoventral topographies that represent the broad position of neuronal cell bodies across the different cortical areas (16)(17)(18). Callosal circuits include connections between largely homotopic regions, as well as heterotopic circuits that importantly include the medial (i.e., cingulate, motor, and retrosplenial cortex) and lateral (i.e., perirhinal cortex, insula, and claustrum) borders of the neocortical sheet (25,(32)(33)(34)(35)(36)(37). These medial and lateral regions also represent hyperconnected hubs within and between hemispheres and form part of the task-negative (also known as default mode) network (25,38).…”
Section: Discussionmentioning
confidence: 99%
“…in (Innocenti and Price, 2005)). In the somatosensory system, CPNs invade the contralateral cortex by P5, reach their maximum density by P10 and then reduce again to reach a stable level of innervation by P20 (Fenlon et al, 2017; De Leon Reyes et al, 2019). Because the establishment of permanent callosal synapses is only finished in the third postnatal week, they might mature based on the network activity generated by already existing ipsilateral connections (Petreanu et al, 2007; Suárez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%